Course of distress in breast cancer patients, their partners, and matched control couples - Hinnen, C; Ranchor, A; Sanderman, R; Snijders, T; Hagedoorn, M; Coyne, J (Springer, 2008)
Background: Previous studies offered a limited perspective on the dynamic course of distress in cancer patients and their partners, owing to a restricted number of assessment points and the absence of comparison controls drawn from the general population. Purpose: This study investigated the course of distress among breast cancer patients and their partners (N=92 couples) in comparison to matched control couples (N=64). Furthermore, the influence of neuroticism on distress was investigated. Method: The Hospital Anxiety and Depression Scale was administered nine times over a 12-month period, and neuroticism was assessed at the beginning of the study using the Eysenck Personality Questionnaire. Results: Multilevel analyses revealed that patients were more distressed during the first 15 months after diagnosis than nonpatients. A significant portion of the distress that could not be explained by the cancer experience was explained by neuroticism. Conclusion: Differences in distress between patients and comparison-control women are relatively small and decreased over time, while distress in male partners was not elevated in comparison to their controls.